Momento magnético anômalo no modelo padrão eletrofraco e além - Cezar Júnior, Alberto de Albuquerque (2019)
We compute some of the main contributions of the Standard Model to the anomalous magnetic moment of charged Dirac fermions and analyze some works accounting for higher order corrections. We compare this with the experimental results that point out a discrepancy between the theoretical prediction and the experiment, which is a strong evidence of physics beyond the Standard Model. We derive the general contributions due to a variety of new particles, considering the possibility of flavor changing and scalar, pseudo-scalar, vector and axial couplings. From these general expressions we retrieve predictions from the Standard Model and additionally we allow the calculation of a vast number of new physics alternatives.